Occupation and Gender - Patricia Cortes; Jessica Pan (Institute of Labor Economics (IZA), 2017)
Occupational differences by gender remain a common feature of labor markets. We begin by documenting recent trends in occupational segregation and its implications. We then review recent empirical research, focusing on new classes of explanations that emphasize the role of gender differences in psychological traits, preferences for non-pecuniary (family-friendly) job characteristics, personality traits, and skills. Using detailed data on occupational work content from O*NET linked to the American Community Survey (ACS), we examine how the various job attributes identified in the literature affect men and women's occupational choices and the gender wage gap. Finally, we consider the role of gender identity and social norms in shaping occupational choice and preferences for various job attributes. We conclude with policy implications and suggestions for future research.
Keywords: J16; J24; 330; gender; occupation; segregation; gender preferences; family-friendly; psychological traits; personality traits; identity